Pesquisa de Aula - Lesson Study: aprendizados e contribuições do Professor Observador em uma sequência didática para o Ensino de frações. - Souza, Wilson Giovani de (2025)
This paper presents the results of our research on the teaching of basic mathematics topics, within the Master’s course in Mathematics Teaching of the Postgraduate Program in Exact Sciences Teaching at UFSCar. The research was based on the author’s experience and reflections on his participation, throughout 2023, in the activities of a research group on the application of Lesson Study in mathematics teaching. The theme of the work focused on the teaching of fractions and their representations, in 6th grade classes at a state school located in a suburb of the city of São Carlos - SP. The results are presented in this paper from the point of view of the Observer Teacher, a role played by the author during the research. This is a role played in the Lesson Study process by the researcher, who is not the teacher of the lessons but a collaborator who critically observes them, according to a lesson plan drawn up collectively in a study group and based on the principles of Lesson Study. This work has shown the lessons learned by the Observer Teacher in the application of a Research Lesson, a central concept in the process of Lesson Study. The analysis of this lesson after it was carried out allowed for the subsequent development of a didactic sequence for teaching fractions at 6th grade level. The sequence was appropriate for the context in which the research was carried out, and is a result of the improvement in the training of teachers who teach in elementary education. The evidence collected through the planned and careful observation of lessons brought meaning to the role of the Observer Teacher in Lesson Study. The research made it possible to see Lesson Study as a methodological alternative for developing teaching practice.